Refining the Rules of the Game: The Corporate Responsibility to Respect Human Rights. Issue 78 (28th February 2014) - Nolan, Justine
The growth of transnational corporations over the past few decades has been paralleled by concerns to find ways of regulating the deleterious impacts on human rights by the ever-increasing number of companies whose corporate tentacles stretch across national boundaries and beyond the reach of traditional corporate control mechanisms. The steady evolution of a global social expectation that companies should respect international human rights standards, combined with the occasional foray by states in adopting an expansive approach to protecting rights, is changing the nature and possibility of developing a firmer basis for corporate accountability for human rights. What we are witnessing is a process of re-regulation whereby state and non-state actors are utilizing a combination of public and private regulation to improve the framework for corporate rights compliance. The regulation of corporate activity with respect to human rights requires a multiplicity of stakeholders and a very nuanced mix of public and private regulation that may be difficult to replicate easily across different sectors, states and cultural boundaries.